Birth of dairy 4.0: opportunities and challenges in adoption of fourth industrial revolution technologies in the production of milk and its derivative - Hassoun, Abdo; Garcia-Garcia, Guillermo; Trollman, Hana; Jagtap, Sandeep; Parra-López, Carlos; Cropotova, Janna; Bhat, Zuhaib; Centobelli, Piera; Aït-Kaddour, Abderrahmane (Elsevier, 2023)
Embracing innovation and emerging technologies is becoming increasingly important to address the current global challenges facing many food industry sectors, including the dairy industry. Growing literature shows that the adoption of technologies of the fourth industrial revolution (named Industry 4.0) has promising potential to bring about breakthroughs and new insights and unlock advancement opportunities in many areas of the food manufacturing sector. This article discusses the current knowledge and recent trends and progress on the application of Industry 4.0 innovations in the dairy industry. First, the “Dairy 4.0” concept, inspired by Industry 4.0, is introduced and its enabling technologies are determined. Second, relevant examples of the use of Dairy 4.0 technologies in milk and its derived products are presented. Finally, conclusions and future perspectives are given. The results revealed that robotics, 3D printing, Artificial Intelligence, the Internet of Things, Big Data, and blockchain are the main enabling technologies of Dairy 4.0. These advanced technologies are being progressively adopted in the dairy sector, from farm to table, making significant and profound changes in the production of milk, cheese, and other dairy products. It is expected that, in the near future, new digital innovations will emerge, and greater implementations of Dairy 4.0 technologies is likely to be achieved, leading to more automation and optimization of this dynamic food sector.
Keywords: Dairies; Industry 4.0; Automation; Smart factory; Real-time monitoring; Artificial intelligence; Big data; IoT; Robotics; Digital technology; 3D printing; Blockchain; Milk; Cheese